(untitled) (Global Journal of Management and Business Research, 2017)
This study aimed to examine the effect of E-Banking service quality on customer satisfaction in the state owned banks in Ethiopia in Debre Markos town. To achieve the objectives of this study, data were collected through questionnaire from a sample of 190 bank customers. These respondents were selected using simple stratified sampling method from both Woreda and zonal level E-Banking users. The data collected from the questionnaire were analyzed using Statistical tools such as mean, standard deviation, correlation, and multiple regression analysis using SPSS version 20. The results of this study indicated that, except assurance the four service quality dimensions (tangibility, reliability, responsiveness and empathy) have positive and significant effect on customer satisfaction. The finding of this study also indicates that customers were most satisfied with the responsiveness dimensions of E-Banking service quality.